Kajian Pembuatan Cupcake dengan Penambahan Tepung Bayam Merah dan Tepung Ikan Teri sebagai Alternatif Makanan Selingan Tinggi Zat Besi dan Kalsium bagi Ibu Hamil - Reni Indriyani; Merita Putri; Arie Nugroho; Nawasari Indah Putri Sejati (Journal of Dietetics Science, 2025)
Cupcake is a snack as a side dish so the nutritional content is limited, it needs other alternatives such as the addition of other food ingredients to increase the nutritional content. The nutritional value of cupcakes can be increased by adding red spinach flour and anchovy flour which have high iron and calcium content. The purpose of this study was to Hetermine the organoleptic properties (color, taste, aroma, texture and overall acceptance) and iron and calcium content of cupcakes with the addition of red spinach flour and the most preferred anchovy flour. The method used is descriptive with one repetition in making the product. Based on the organoleptic test, it was found that the most preferred cupcake with the addition of red spinach flour and anchovy flour was formula 1 with the addition of red spinach flour and anchovy flour as much as 8%. The results of the iron analysis of cupcakes with the addition of red spinach flour and anchovy flour using TKPI amounted to 1.28 mg, while based on laboratory tests the iron content was found to be 8.7 mg. It is necessary to conduct a shelf life best to determine the shelf life of the cupcake can be consumed. When mixing melted butter, it must be ensured that it is evenly mixed so that the cupcake expands perfectly.